Neurological Soft Signs in Schizophrenia: An Update on the State- versus Trait-Perspective - Bachmann, Silke; Schröder, Johannes (Frontiers in Psychiatry, 2018)
Background: Neurological soft signs (NSS) represent minor neurological signs which indicate non-specific cerebral dysfunction. In schizophrenia, their presence has been documented extensively across all stages of the disease. Until recently NSS were considered an endophenotype or a trait phenomenon. During the past years, however, researchers report fluctuations of the NSS scores. Aims: To further clarify the question whether NSS exhibit state or trait components or both, studies that have investigated NSS longitudinally were reviewed. Method: Studies which have assessed NSS longitudinally in adults suffering from schizophrenia, were searched for. The time frame was January 1966 to June 2017. Studies on teenagers were excluded because of interferences between brain maturation and pathology. Results: Twenty-nine follow-up studies were identified. They included patients during different stages of their illness and mainly used established instruments for NSS assessment. Patients with a first episode or a remitting course predominantly show a decrease of NSS over time, whereas a worsening of NSS can be found in the chronically ill. It was shown that change of NSS total scores over time is predominantly caused by motor system subscales and to a lesser extent by sensory integration scales. With respect to medication the majority of studies agree on a relationship between medication response and improvement of NSS while the type of antipsychotic does not seem to play a major role. Moreover, where information on side-effects is given, it does not favour a strong relationship with NSS. However, NSS seem to correlate with negative and cognitive symptoms. Conclusions: Studies manifest a conformity regarding the presence of NSS in schizophrenia patients on the one hand. On the other hand, fluctuations of NSS scores have been widely described in subgroups. Taken together results strongly support a state-trait dichotomy of NSS. Thus, the usage of NSS as an endophenotype has to be called into question.